2015
DOI: 10.1002/hed.24050
|View full text |Cite
|
Sign up to set email alerts
|

Early oral cancer diagnosis: The Aarhus statement perspective. A systematic review and meta‐analysis

Abstract: A longer time interval from first symptom to referral for diagnosis is a risk factor for advanced stage and mortality of oral cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E2182-E2189, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 52 publications
0
90
0
Order By: Relevance
“…Many risk factors for OC have been described, but smokeless and smoking tobacco, alcohol, and viral infection especially human papillomavirus (HPV) are among the fundamental factors for disease occurrence (Johnson et al, ; Somatunga et al, ). The diagnosis of OC in the early stage and subsequently early intervention with the required therapy have a positive impact on increasing the rate of survival up to 5 years (Lopez‐Jornet et al, ; Seoane et al, ; Tax et al, ). Fortunately, OC is one of the disease that can be discovered in the early stage through routine visual and tactile inspection of oral mucosa (Colella, Gaeta, Moscariello, & Angelillo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many risk factors for OC have been described, but smokeless and smoking tobacco, alcohol, and viral infection especially human papillomavirus (HPV) are among the fundamental factors for disease occurrence (Johnson et al, ; Somatunga et al, ). The diagnosis of OC in the early stage and subsequently early intervention with the required therapy have a positive impact on increasing the rate of survival up to 5 years (Lopez‐Jornet et al, ; Seoane et al, ; Tax et al, ). Fortunately, OC is one of the disease that can be discovered in the early stage through routine visual and tactile inspection of oral mucosa (Colella, Gaeta, Moscariello, & Angelillo, ).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these difficulties, the Aarhus guidelines have suggested standardised time intervals within a conceptual framework and the abandonment of the term “diagnostic delay.” The events considered in this model (detection of bodily changes, perception of reasons to discuss symptoms with a healthcare professional, first consultation with a healthcare professional, diagnosis and treatment start) define four single time intervals (appraisal, help‐seeking, diagnostic and pre‐treatment) . This framework is dynamic and bidirectional, without a pre‐defined starting point, and allows multiple paths to reach the final diagnosis . This permits the design and monitoring of interventions aimed at decreasing the time elapsed since the first symptom/sign until the treatment is implemented, improving this way the prognosis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…11 This framework is dynamic and bidirectional, without a pre-defined starting point, and allows multiple paths to reach the final diagnosis. 11,12 This permits the design and monitoring of interventions aimed at decreasing the time elapsed since the first symptom/sign until the treatment is implemented, improving this way the prognosis of the disease. The Aarhus Statement suggests a "model of pathways to treatment" which considers as contributing factors those that depend on the patient, on the healthcare provider (HCP) and on the healthcare system, taking also into account those factors related to the tumour itself.…”
mentioning
confidence: 99%
“…6,11 Education and periodic surveillance as part of a screening activity can raise awareness and thereby lead to detection of asymptomatic lesions. 18 Thanks to the high coverage rate of national health insurance in Taiwan, this study cohort could be readily referred to specialists for prompt diagnosis and treatment. 17 A metaanalysis study indicated that more oral carcinomas can be detected at an early stage if the diagnostic delay in primary care is shortened.…”
Section: Discussionmentioning
confidence: 99%